Orthopalladated N, N-dimethyl-1-phenethylamine compounds containing 2, 6-lutidine: Synthesis, DNA binding studies and cytotoxicity evaluation. (1st January 2023) - Zanetti, Renan D.; da Cunha, Gislaine A.; Moreira, Mariete B.; Farias, Renan L.; de Souza, Ronan F.F.; de Godoy, Paulo R.D.V.; Brassesco, María Sol; Rocha, Fillipe V.; Lima, Mauro A.; Mauro, Antonio E.; Netto, Adelino V.G.
Graphical abstract: New cyclopalladated compounds were synthesized and their antiproliferative activities against some human tumor cell lines were similar to those of cisplatin. The complexes displayed no significant binding with DNA and were unable to inhibit topoisomerase II activity. Studies showed that human serum albumin (HSA) can transport these compounds. Abstract: Metathetical reactions involving [Pd( C 2, N -dmpa)(μ-Cl)]2 (1 ) and the appropriate halides/pseudohalides salts afforded cyclopalladated dimers of the type [Pd( C 2, N -dmpa)(μ-X)]2 (dmpa =  S (−) enantiomer of N, N -dimethyl-1-phenethylamine; {X = Cl (1 ) and N3 (2 )}. Mononuclear compounds of general formulae [Pd( C 2, N -dmpa)(X)(lut)] {X = Cl (1a ) and N3 (2a )} were obtained by bridge-splitting reactions involving the corresponding [Pd( C 2, N -dmpa)(μ-X)]2 with 2, 6-lutidine (lut) in the 1:2 M ratio at room temperature. Both the cyclopalladated compounds were characterized by means of elemental analysis, FT-IR, Raman, 1 H and 13 C NMR spectroscopy. The antiproliferative activity of the mononuclear compounds 1a -2a was evaluated towards human glioblastoma (U251 and T98G) and melanoma cell lines (HT144 and LB373) and their IC50 values determined between 1 and 6 μM. In most cases, the cytotoxic effects of compounds 1a -2a showed to be similar to those of cisplatin (depending on the cell line), what is of utmost importance when considering treatment alternatives for these aggressive tumor types. Binding studies on the representative compound 2a towards ct-DNA, however, showed low or no affinity, suggesting that the observed cytotoxicity against the human cell lines may involve different mechanisms of action compared to that of the platinum-based chemotherapy drug. The ability of 1a to induce the inhibition of topoisomerase IIα activity has also been investigated. These cyclopalladated compounds can be transported and distributed through the body by human serum albumin (HSA), as observed by competition and computational studies with the protein. These findings are very promising and have motivated further studies for the design of new and bioactive cyclopalladated compounds for future medicinal purposes.